Transfer mechanisms and strategic knowledge management in health and safety companies (2019)
(Eng) This paper aims to analyse the knowledge transfer mechanisms and strategic knowledge management in occupational safety and health (OSH) companies. The main authors consulted for the study were Dav - enport (6) , Molina, and Marsal (8) . The research is descriptive, non-experimental, cross-sectional and with field design. Results indicate that the spontaneous transference is present through personal meetings, and formal transference is mainly characterized by counselling. We found weaknesses in the strategic analysis and objectives definitions for the strategic knowledge management in the studied or ganizations.